Maximizing Faculty Performance - Mary Devine (Academic Chairpersons Conference Proceedings, 2019)
This session will explore the ways that we can support faculty to be innovative and achieve high standards of student service, and will provide you with strategies for helping faculty to stay ‘on track’ with department goals. Engaging and motivating part-time faculty will also be covered in the workshop. Connect with fellow chairs to share and be inspired by the practice of other chairs as they strive maximize faculty performance.
Keywords: Academic Leadership; Reflective Practice; Leadership Development; High-performing teams; Leadership Values